Pengaruh Model Problem Based Learning untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Rantai Makanan di Kelas V SD Negeri Tuak Daun Merah - Mite, Karolus; Antonius Suban Hali; Rista Aprilya Devi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of Natural and Social Sciences (IPAS) on the food chain material in grade V of SD Negeri Tuak Daun Merah. The main cause is the conventional and teacher-centered learning process through lecture methods, so that students become passive and quickly bored. This study aims to test the significance of the effect of the application of the Problem Based Learning (PBL) model in improving student learning outcomes on the material. This type of research is quantitative with a pre-experimental design approach of one-group pre-test–post-test type. The study population includes all grade V students totaling 67 people. The sampling technique used purposive sampling, so that class VB, totaling 23 people, was selected as the sample. Data collection used an objective multiple-choice test instrument of 20 questions through pre-test and post-test. The instrument was declared reliable with a Cronbach's Alpha coefficient of 0.960. The data were analyzed using prerequisite tests in the form of the Shapiro-Wilk normality test with a pre-test significance value of 0.178 and a post-test of 0.116 (normally distributed), as well as the Levene Statistic homogeneity test with a significance value of 0.143 (homogeneous). Based on the hypothesis test using the Paired Samples T-Test assisted by SPSS version 27, a significance value (2-tailed) of 0.001 was obtained. Because 0.001 < 0.05, H₀ was rejected and Hₐ was accepted, proving an empirically significant effect. The increase in learning outcomes was indicated by the average pre-test value of 58.26 which increased to 86.74 in the post-test. In addition, the results of the effect size test using Cohen's d obtained a value of 2.744, which is included in the very large effect category. These results indicate that the implementation of the Problem-Based Learning (PBL) model not only has a statistically significant effect but is also highly effective in improving student learning outcomes in the food chain topic. In conclusion, the PBL model has a positive, significant, and highly significant effect on improving student learning outcomes in the sciences subject of the food chain. Keywords: Problem-Based Learning, learning outcomes, food chain.